Cranial Tip Suture in Nasal Tip Contouring - Kovacevic, Milos; Wurm, Jochen (Facial Plastic Surgery, 2014)
The creation of both a functionally and aesthetically pleasing nasal tip contour is demanding and depends on various different parameters. Typically, procedures are performed with emphasis on narrowing the nasal tip structure. Excisional techniques alone inevitably lead to a reduction in skeletal support and are often prone to unpredictable deformities. But also long-term results of classical suture techniques have shown unfavorable outcomes. Particularly, pinching of the ala and a displacement of the caudal margin of the lateral crus below the cephalic margin belong to this category. A characteristic loss of structural continuity between the domes and the alar lobule and an undesirable shadowing occur. These effects lead to an unnatural appearance of the nasal tip and frequently to impaired nasal breathing. Stability and configuration of the alar cartilages alone do not allow for an adequate evaluation of the nasal tip contour. Rather a three-dimensional approach is required to describe all nasal tip structures. Especially, the rotational angle of the alar surface as well as the longitudinal axis of the lateral crus in relation to cranial septum should be considered in the three-dimensional analysis. Taking the various parameters into account, the authors present new aspects in nasal tip surgery which contribute to the creation of a functionally and aesthetically pleasing as well as durable nasal tip contour.
Keywords: cranial tip suture; alar surface septal angle; nasal tip contour; broad nasal tip; pinched nose